2019
DOI: 10.1371/journal.pone.0214012
|View full text |Cite
|
Sign up to set email alerts
|

Missed opportunities for earlier diagnosis of HIV in British Columbia, Canada: A retrospective cohort study

Abstract: BackgroundLate HIV diagnosis is associated with increased AIDS-related morbidity and mortality as well as an increased risk of HIV transmission. In this study, we quantified and characterized missed opportunities for earlier HIV diagnosis in British Columbia (BC), Canada.DesignRetrospective cohort.MethodsA missed opportunity was defined as a healthcare encounter due to a clinical manifestation which may be caused by HIV infection, or is frequently present among those with HIV infection, but no HIV diagnosis fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 33 publications
0
29
0
6
Order By: Relevance
“…Similar results are reported elsewhere. 1921,23,3133 We found that not testing for HIV at a clinical encounter often resulted in a significantly lower CD4 cell count at the time of eventual HIV diagnosis and a very high (80%) rate of PLHIV who had experienced an HCIC becoming late presenters. A high proportion of late presenters with prior missed indicator conditions has also been reported by others.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Similar results are reported elsewhere. 1921,23,3133 We found that not testing for HIV at a clinical encounter often resulted in a significantly lower CD4 cell count at the time of eventual HIV diagnosis and a very high (80%) rate of PLHIV who had experienced an HCIC becoming late presenters. A high proportion of late presenters with prior missed indicator conditions has also been reported by others.…”
Section: Discussionmentioning
confidence: 83%
“…21,22 In British Columbia, Canada, 14% of individuals living with undiagnosed HIV between 2001 and 2014 had a clinical encounter for a condition associated with a high HIV prevalence without being tested, resulting in a missed opportunity for an earlier HIV diagnosis. 23 Despite decade-old recommendations, routine testing for HIV in a clinical setting has still not been achieved especially in those individuals who were perceived to be at lower HIV risk even when presenting with illnesses suggestive of HIV infection. 24 One study identified 41 factors reported by physicians as being barriers to enhanced routine HIV testing including insufficient time, burdensome consent processes, lack of patient acceptance, lack of knowledge and training regarding testing, and competing priorities.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] In this pilot, PLWH for whom MO were identified were more likely to be white, and UK-born, consistent with other studies suggesting that individuals born in high-income countries may be inaccurately presumed to be low risk for HIV by healthcare providers when they present without apparent risk factors. 19,20 Data on the nature of MO were not specifically collected, however the most common indicator conditions identified were mononucleosis-like illness, recurrent leukopenia or thrombocytopenia, recurrent shingles, candidiasis, lymphadenopathy and weight loss. Specific training programmes to increase HIV testing awareness should address this misconception, particularly in high prevalence regions.…”
Section: Effectiveness Of the Pilot Processmentioning
confidence: 99%
“…Так, за результатами опитувань лікарів загальної практики та лікарів -інфекціоністів відмічалось, що лікарі загальної практики з великим досвідом управління ВІЛ-інфекцією надавали якісну допомогу цим складним пацієнтам [13]. Особливо важливо, що саме сімейні лікарі можуть знизити так звані втрачені можливості для раннього діагностування ВІЛ, до яких відносяться вчасний контакт із системою охорони здоров'я через клінічний прояв, який може бути спричинений ВІЛ-інфекцією, або часто виникає серед людей, що мають ВІЛ-інфекцію, але без встановлення діагнозу ВІЛ упродовж 30 днів [14]. Підкреслюється важливість в умовах широкого розповсюдження ВІЛ-інфекції та інших гемоконтактних інфекцій посилення поглибленої підготовки сімейних лікарів з питань ведення пацієнтів з ВІЛ-інфекцією та необхідність проведення постійного їх навчання щодо сучасних керівництв, протоколів, настанов з різних питань ВІЛ-інфекції [15] [16].…”
Section: вступunclassified